2010
DOI: 10.1186/1479-5868-7-75
|View full text |Cite
|
Sign up to set email alerts
|

Variation in mode of physical activity by ethnicity and time since immigration: a cross-sectional analysis

Abstract: BackgroundPhysical activity (PA) levels are known to be significantly lower in ethnic minority and immigrant groups living in North America and Europe compared to the general population. While there has been an increase in the number of interventions targeting these groups, little is known about their preferred modes of PA.MethodsUsing three cycles of the Canadian Community Health Survey (cycles 1.1, 2.1, 3.1; 2000-2005, n = 400,055) this investigation determined PA preferences by self-ascribed ethnicity (Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 21 publications
3
77
2
1
Order By: Relevance
“…In terms of race effects on other dependent variables, households of Hispanic race make fewer motorized tours, while households of Asian race make fewer nonmotorized tours. A few earlier studies (see Allen et al, 2007 andDogra et al, 2010) in the public health field also have observed that Asian households tend to be less physically active in terms of non-motorized recreation pursuits (such as walking and bicycling around the neighborhood).…”
Section: Exogenous Variable Effectsmentioning
confidence: 99%
“…In terms of race effects on other dependent variables, households of Hispanic race make fewer motorized tours, while households of Asian race make fewer nonmotorized tours. A few earlier studies (see Allen et al, 2007 andDogra et al, 2010) in the public health field also have observed that Asian households tend to be less physically active in terms of non-motorized recreation pursuits (such as walking and bicycling around the neighborhood).…”
Section: Exogenous Variable Effectsmentioning
confidence: 99%
“…The association between physical activity and consumption of sweetened products requires further examination especially in very active individuals who may overuse sweetened products as the main source of energy while exercising. This is important considering that Middle East Canadians report one of the lowest levels of physical activity in the country (21,22) . The study also has implications for migrant health studies.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Forty-two self-declared normoglycaemic individuals (twenty-five women, seventeen men) evenly distributed across age groups (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) (33) ; an exclusion cut-off of .6?5 % was applied (34) . The research protocol was submitted and approved by the ethics committee of the Centre Hospitalier de l'Université de Montréal (SL 06-063).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in this literature review also examined the existence of ethnic minority clubs and how some minority women left majority clubs to be a part of minority ones because of better understanding and comfort in their own cultural groups. Dogra, Meisner, and Ardern (2010) investigated the variation in mode of PA by ethnicity and time since immigration through a cross-sectional analysis using three cycles of the Canadian Community Health Survey (CCHS) from 2000-2005 with a total of 400,055 participants. The researchers found ethnic minorities as the least likely to engage in endurance activities, recreation activities such as gardening or dancing and sports compared to Whites.…”
Section: Physical Activitymentioning
confidence: 99%